(untitled) (Journal of Applied Learning and Teaching, 2024)
The post-anthropocentric concept of posthumanism decentralizes human experiences and dismantles absolute human agency. This is done by endorsing the importance of relationality between various human, non-human, material and abstract elements in constituting/composing experiences, events or matters. In education, posthumanist philosophy envisages an inclusive, interdisciplinary perspective that endorses the human and non-human agencies dynamically engaging in material and abstract relations, inside as well as outside the classroom, to reconstruct the traditional pedagogies that focus on texts, teachers and the lack of learner agency. Conceived in the qualitative paradigm, the present study attempts to examine the role of learner agency, motivation, and the affect of assemblages in developing the speaking proficiency of tertiary-level learners in an English for Specific Purposes (ESP) classroom in India. As part of the intervention, learners created wordless graphic assemblages (in groups) with arbitrary images using an online digital comic builder platform to create stories. Their post-task activities, such as discussions, hypothetical questioning, and Socratic seminars oriented towards the development of their speaking proficiency, were analysed. The findings of the study show that graphic assemblages can be used as an effective posthuman pedagogical tool to enhance learners’ speaking skills and operationalize their higher-order thinking skills. It also augments agency, facilitates affect, and increases motivation among learners. The results of the study suggest that the graphic assemblages fulfil different teaching and learning objectives. It also provides scope for educators to formulate more strategies that involve creative practices in a language classroom using a posthuman educational perspective.